Evaluation of the Effect of Palashadi Varti in the management of Shweta Pradara (Abnormal Vaginal Discharge) on Clinical Parameters (AYUSHDHARA, 2025)
Abnormal Vaginal Discharge can be correlated to Shweta Pradara is detailed in texts like Sharagdhar Samhita, Bhavprakash, and Yogratnakar. Commentator Chakrapani has explained the word Pandura-Asrigdara as Shwetapradar in his commentary on Charak Samhita. This condition often signals underlying genital tract pathologies and may present as thick, viscid, and foul-smelling discharge, particularly when caused by infections. Common pathogens include Gardnerella, Chlamydia, Trichomonas, and Candida albicans. AIM & OBJECTIVES: To assess the effect of the trial drug Palashadi Varti in the Management of Shwetapradar and to evaluate the comparative efficacy of the trial drug with modern drug. MATERIAL & METHODS: With Ethical Committee approval and informed consent, 210 patients were randomly assigned to two groups. In one group, Palashadi Varti at night was given for 7 days. From baseline to 7th day based on assessment criteria per-speculum examination was done. A comparison of categorical variables was done using an appropriate statistical test. RESULTS: Palashadi Varti potentially had comparable effects to the conventional treatment but the recurrence rate was found more in conventional treatment. CONCLUSION: Palashadi Varti is an effective, side effects-free, patient-complaint herbal alternative for the management of abnormal vaginal discharge.